100 Years of Geothermal Power Production - Lund, John W. (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 2004)
Electricity from geothermal energy had a modest start in 1904 at Larderello in the Tuscany region of northwestern Italy with an experimental 10 kW-generator. Today, this form of renewable energy has grown to 8771 MW in 25 countries producing an estimated 54,793 GWh/yr. These “earth-heat” units operate with an average capacity factor of 71%; though, many are “on-line” over 95% of the time, providing almost continuous base-load power. This electricity production is serving an equivalent 60 million people throughout the world, which is about one percent of our planet’s population. The large downward spike in the production is the result of the destruction of the Italian field at the end of World War II–discussed later